Compositional dependence of thermal transport and optical properties of Se85 Ge15-x Pbx (0≤ x ≤10) chalcogenide glassy alloys - Mishra P.K.; Singh K.; Upadhyay A.N.; Kumar H. (My University, 2025)
In the present work, the ratio of germanium (Ge) to lead (Pb) is varied keeping the concentration of selenium(Se) fixed in the glassy system, Se85 Ge15-x Pbx (0 ≤ x ≤ 10) to optimize the thermal transport and optical properties. The differential scanning calorimetry (DSC) measurements were carried out in the non-isothermal mode to know glass transition temperature (Tg), crystallization temperature (Tc) and melting temperature (Tm). DSC scans of some samples(4 ≤ x ≤ 10) exhibit two glass transition temperatures (Tg), which indicates the presence of co-existing phases in glassy samples. The values of effective thermal conductivity (λe),effective thermal diffusivity(χe) and volumetric heat capacity(QCp) have been determined using transient plane source (TPS) measurements. These parameters show a non-monotonous behavior with the variation of Pb content in the prepared series. These results are explained in terms of chemical bond approach, changes in thermal transfer processes and mechanism of phonon scattering under transitions from dilute to concentrated solid solution. Band gap and Urbach energy have been estimated using Uv–Vis spectroscopy. Optical band gap (~0.65 eV) is minimum for the sample having 4 at.% of Pb. A signature of exciton formation is obtained for this critical composition. Results are explained using structural defect model and by degree of disorder induced, as indicated by a change in intensity and position of the Raman peak corresponding to Se–Se bonds. © 2019 Elsevier B.V.